An updated overview about the synthesis, scaling-up and applications of double nanoemulsions (2022)
Nanoemulsions are nano-sized emulsified systems. They can be produced by different methods, which can be classified as low and high-energy methods. The decrease in the size of formed globules allows them to penetrate different barriers such as the skin or the gastrointestinal barrier. Thus, the encapsulation of active compounds through nanoemulsions makes it possible to improve their bioavailability and to offer protection against environmental conditions such as temperature, humidity, or UV radiation. In the same way, it is possible to formulate double nanoemulsions to encapsulate hydrophilic and lipophilic molecules in one single globule. Their formulation process requires a comprehensive analysis involving physical and thermodynamic approaches. .